Investigating Pipe Culvert Failure in Baleela Oil Field in Sudan - S. M. Hamza, Omer; E. Eltybe, Zain; M. Omer, Omer (University of Khartoum Engineering Journal, 2022)
This paper thoroughly investigates failure cases of the constructed pipe culverts in Baleela oil field in west of Sudan. The paper provides technical recommendations and remedial measures. Common types of failures of pipe culverts and their appropriate measures were briefly discussed. The paper provides inspection based on extensive site survey and data record review to find out the main structural and hydrological causes of culverts failure. The site survey is conducted in the last two years while the data record review extended since 2011. The pipe culverts engaged in this study were 20 water streams each of them contain 3 to 8 pipe culverts. Failures of pipe culverts constructed in 9 locations during the last 9 years were evaluated in percentage. The investigation showed that various reasons caused failures of the studied culverts including volume of water flow, corrosion and scouring, floating trees and deformation in pipe culvert obtained from traffic load beside construction related reasons such as culverts assembly, poor construction, un-compacted backfilling and the backfilling soil type in addition to design related reasons such as improper design and pipe capacity. It could be concluded that the pipe culvert is the most economic water crossing structures for valleys of low water flow volume. Also pipe culverts are not suitable for wide shallow valleys.